Cetuximab plus XELOX show efficacy against brain metastasis from colorectal cancer: a case report - Ahmad KH Ibrahimi; Maysa Al-Hussaini; Dima Abu Laban; Rula Ammarin; Lina Wehbeh; Abdelatif Al-Mousa (CNS Oncology)
Brain metastasis (BM) from colorectal cancer (CRC) is rare and associated with poor prognosis. The mainstay of treatment for BM from CRC is radiotherapy, systemic treatment options for CRC can include novel targeted agents, conventional chemotherapy or a combination of both. Nevertheless, the efficacy of these systemic treatment options against BM from CRC is not yet fully established. Cetuximab, a monoclonal antibody, has been shown to be effective in patients with KRAS wild-type metastatic CRC. The combination of cetuximab with oxaliplatin-based chemotherapy is commonly utilized as a systemic treatment for metastatic CRC. Hereby, we report a case of BM from CRC with significant response after capecitabine and oxaliplatin (XELOX) combined with cetuximab.